Epidemiological investigation and successful management of a Burkholderia cepacia outbreak in a neurotrauma intensive care unit. (February 2019) - Rastogi, Neha; Khurana, Surbhi; Veeraraghavan, Balaji; Yesurajan Inbanathan, Francis; Rajamani Sekar, Suresh Kumar; Gupta, Deepak; Goyal, Keshav; Bindra, Ashish; Sokhal, Navdeep; Panda, Ashutosh; Malhotra, Rajesh; Mathur, Purva
Abstract: Objective: The detailed epidemiological and molecular characterization of an outbreak of Burkholderia cepacia at a neurotrauma intensive care unit of a level 1 trauma centre is described. The stringent infection control interventions taken to successfully curb this outbreak are emphasized. Methods: The clinical and microbiological data for those patients who had more than one blood culture that grew B. cepacia were reviewed. Bacterial identification and antimicrobial susceptibility testing was done using automated Vitek 2 systems. Prospective surveillance, environmental sampling, and multilocus sequence typing (MLST) were performed for extensive source tracking. Intensive infection control measures were taken to further control the hospital spread. Results: Out of a total 48 patients with B. cepacia bacteraemia, 15 (31%) had central line-associated blood stream infections. Two hundred and thirty-one environmental samples were collected and screened, and only two water samples grew B. cepacia with similar phenotypic characteristics. The clinical strains characterized by MLST typing were clonal. However, isolates from the water represented a novel strain type (ST-1289). Intensive terminal cleaning, disinfection of the water supply, and the augmentation of infection control activities were done to curb the outbreak. A subsequent reduction in bacteraemia cases was observed. Conclusion: Early diagnosis and appropriate therapy, along with the rigorous implementation of essential hospital infection control practices is required for successful containment of this pathogen and to curb such an outbreak.